Analytic hierarchy process applied to landslide susceptibility mapping of the North Branch of Argentino Lake, Argentina - Moragues, Silvana Noelia (2020)
In the present study, we achieved the susceptibility mapping to slope instability processes by the implementation of Analytic Hierarchy Process and Weighted Linear Combination methods, in the North Branch of Argentino Lake, Southern Patagonian Icefield. The strong retraction of the glaciers in the area has triggered paraglacial readjustments, producing instability processes that favor the generation of mass removal processes. The results obtained from optical satellite images show that the highest degrees of susceptibility (4 and 5) are located on the western slopes of the Upsala Channel, Bertacchi and Cono Tributary Glaciers, and the Moyano and Norte Valleys, respectively. These slopes coincide with the geographic location of previous events surveyed by the inventory of unstable areas of the zone. Low degrees of susceptibility are found on the downhill valleys, outcrops rock and glaciers. The Consistency Ratio was 0.069, indicating that being less than 0.1 the study is reliable. The study sheds light on the knowledge of slopes and valleys that are more susceptible to processes of instability in mountainous areas, which would make it possible to prevent possible hazards associated with these events.